Test, Trace, and Treatment Strategy to Control COVID-19 Infection Among Hospital Staff in a COVID-19 Referral Hospital in Indonesia - Rakhmad Hidayat; Nurul Aini; Azizah Fitriana Nurul Ilmi; Faiza Azzahroh; Astuti Giantini (Acta Medica Indonesiana)
Background: COVID-19 infection is caused by a novel coronavirus. One of the most used strategies that can be used to control the spread of COVID-19 is the 3T (test, trace, and treatment) strategy. This study aimed to evaluate the 3T strategy to control COVID-19 infection in a COVID-19 Referral Hospital in Depok, West Java, Indonesia. Methods: this is a cross-sectional study conducted at the University of Indonesia Hospital. The study was conducted in June 2020 with 742 participants (staff members) using secondary data from polymerase chain reaction (PCR) test results. We presented data in the descriptive form and performed bivariate analysis using the chi-square/Fischer test for categorical data. Results: the PCR test results were positive in 83 (11.1%) participants, with a case-per-tracing ratio of 1:24 and 1:2 in the first and third phases of tracing, respectively. The COVID-19 case graph for the participants decreased along with the implementation of the 3T strategy. The positivity rate in the first phase of tracing was 20% and decreased to 5% in the third phase of tracing. Staff with confirmed positive test results were advised to isolate themselves (hospital or self-isolation). Hospital isolation was found to be associated with the duration of PCR test conversion (p<0.001). Conclusion: the 3T strategy is effective for controlling the spread of COVID-19. The strategy should be implemented simultaneously with other health precautions to reduce the risk of spreading infection.